2005
DOI: 10.1363/3706205
|View full text |Cite
|
Sign up to set email alerts
|

Worksite-Based Parenting Programs to Promote Healthy Adolescent Sexual Development: A Qualitative Study Of Feasibility and Potential Content

Abstract: A worksite-based program designed to help parents of adolescents develop communication and parenting skills could provide a way to reach busy parents. Recommendations from parents, employers and teenagers can be used to make such a program appealing and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Many of our findings are consistent with those of previous studies 9,11–17,22–24 . However, our study reveals complexities in parents’ attitudes not reported elsewhere.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Many of our findings are consistent with those of previous studies 9,11–17,22–24 . However, our study reveals complexities in parents’ attitudes not reported elsewhere.…”
Section: Discussionsupporting
confidence: 93%
“…Qualitative research has helped to provide a deeper understanding of the barriers to effective parent‐child communication, as perceived by parents themselves. Barriers to communication identified by parents have included children’s resistance to communication because they feel it invades their privacy, parents’ difficulty in acknowledging that their children might be sexually active and parents’ lack of role models because their own parents did not talk to them about sex 14–16 . Parents have also described strategies they have used to overcome the barriers to communication, such as reading to enhance their own knowledge of the topic, asking their children about the material covered in sex education classes and using events from real life or TV shows as conversation starters 14–16 …”
mentioning
confidence: 99%
“…18 Parents report feeling embarrassed, 19 inadequately informed, 19 and unsure of what to say or how to begin. 20 Parents who feel more confident in their ability to communicate with adolescents are more likely to engage in conversations about sex. 18 19 Programmes that increase parents' comfort and communication skills related to sexual matters have the potential to change adolescent behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Additional details about the program's design and parent and adolescent outcomes are available elsewhere. 6,12,13 The institutional review boards of RAND and the University of California, Los Angeles approved the study protocol.…”
Section: Methodsmentioning
confidence: 99%
“…5 Parents often cite feeling poorly informed, embarrassed, or unsure of what to say or how to begin. 6,7 Programs that teach parents how to communicate about sexual health with their children have been demonstrated to improve parental confidence in initiating conversations with their children about sex, 8-10 but parents often have difficulty enrolling in these programs because of scheduling and location issues. 11 This is particularly true for employed parents.…”
Section: Introductionmentioning
confidence: 99%